Joint Effects of Host Genetic Background and Mycobacterial Pathogen on Susceptibility to Infection - Di Pietrantonio, Tania (American Society for Microbiology, 2011)

(untitled)
The present study examined the differential contribution of host genetic background and mycobacterial pathogen variability to biological and mechanistic phenotypes of infection. For this purpose, A/J and C57BL/6J mice were infected intravenously with a low dose of Mycobacterium tuberculosis H37Rv or the Russia, Japan, and Pasteur substrains of Mycobacterium bovis bacille Calmette-Guérin (BCG). The pulmonary bacterial counts (number of CFU) and transcript levels of select cytokines (e.g., Ifng, Il12b, and Il4) at 1, 3, and 6 weeks postinfection were measured as biological and mechanistic phenotypes, respectively. The individual and combined impact of the host and mycobacteria on these phenotypes was assessed using three-way analysis of variance (ANOVA), which partitions phenotypic variation into host, pathogen, time, and interaction effects. All phenotypes, except pulmonary Il4 transcript levels, displayed evidence for host-mycobacterium specificity by means of significant interaction terms. Pulmonary expression profiles of 34 chemokines and chemokine-related genes were compared across the hosts and mycobacteria. The differences in induction of these immune messenger genes between A/J and C57BL/6J mice were modest and generally failed to reach significance. In contrast, the mycobacteria induced significant variance in a subset of the immune messenger genes, which was more evident in A/J mice relative to that in C57BL/6J mice. Overall, the results demonstrated the importance of considering the joint effects of the mycobacterial and host genetic backgrounds on susceptibility to mycobacterial infections.